Postharvest quality of organic vegetables grown in the highlands of northern Thailand - Boonyakiat D. (2014)
The postharvest quality of organic vegetables, which included cabbage, spinach and cos lettuce, was studied and compared with that of vegetables grown under the conventional system. These vegetables were stored at 0°, 4°, 8°C and room temperature. The physico-chemical quality of cabbage was analyzed every 2 days. The results showed that cabbage and spinach grown under the conventional system had a longer shelf life than those grown under an organic condition. The storage life of organic cos lettuce was not significantly different from cos lettuce grown under the conventional system. The L value, chroma, hue, total soluble solids and phenolic compounds of organic cabbage were not significantly different from that of the conventionally grown ones. However, organic cabbage contained lower vitamin C level and chlorophyll a content. The storage life of vegetables at low temperature was longer than their storage life at room temperature.